Implementation of Detonator Trigger Control System-Based on Smart Relay to Support Ammunition Disposal - Wira Ahmad Samsudin; Arontino Prakoso (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
In munitions disposal, challenges can sometimes pose risks to personnel or damage equipment. To address this, a smart relay system was developed to create and testrol system to support munitions disposal in military operations. This research used an experimental approach, where the system was tested at various distances and environmental conditions. The testing aimed to measure response speed, relay activation success rate, and signal range. The results showed that the smart relay system could operate with a fast response time up to a distance of 250 meters, with a success rate of 98% in the laboratory and 96% in outdoor conditions. However, the system still faces challenges regarding signal range and battery life, especially at distances over 400 meters or in extreme environmental conditions. In conclusion, this control system is effective and efficient in enhancing the safety of munitions disposal. However, further development is needed to extend the signal range and optimize battery life. Integrating stronger communication technology and more efficient batteries is recommended to improve the system's stability and performance in the field.